ANALISIS TINGKAT KEPUASAN MAHASISWA TERHADAP PELAYANAN PRIMA (EXCELLENT SERVICE) PADA E-COMMERCE SHOPEE (STUDI KASUS PADA MAHASISWA UNIVERSITAS SILIWANGI TASIKMALAYA) - Sihotang, Mey A.; Rulistiani, Anita; Nurfatimah, Mila (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
This study aims to determine the level of goals for Excellent Service at Shopee E-Commerce. The research method used in this study is a qualitative method using a descriptive analysis approach. The data collection technique used a survey in the form of a questionnaire distributed to the object of research via google form. The research sample was taken using a simple random sampling technique, in this study the number of respondents was 50 students of the University of Siliwangi who used the Shopee application. Based on the research, it was revealed that the level of student satisfaction with Excellent Service at E-Commerce Shopee was Satisfied. This is because most of them, as many as 68% of students are satisfied with the service when shopping at Shopee. While some others, namely 14% felt very satisfied and 9% of students felt neutral with the services provided when shopping at Shopee.